The meaning of sexuality for the spouse caregiver of the elderly person with Alzheimer’s disease - Sales, Marta Gabriele Santos; Menezes, Tânia Maria de Oliva (Rev Rene, 2017)
Objective: to understand the meaning of sexuality for the spouse caregiver of the elderly person with Alzheimer’s disease. Methods: qualitative study with eight spouses of elderly Alzheimer’s patients by means of semi-structured interviews in households. The content analysis technique was used for systematic analysis of interviews and categorization of statements. Results: two categories were seized: 1. Understanding of sexuality; 2. Meaning of sexuality after the Alzheimer’s disease of the spouse. The testimonials revealed a lack of knowledge about the term “sexuality”, as well as the shame of talking about the subject. Sexuality was present in the lives of some and abolished in the lives of others. Conclusion:there are positive and negative aspects of the impact of the disease on sexuality. They make this population vulnerable to various conflicting situations with the self and with the marital relationship.